2017
DOI: 10.1108/ijlss-06-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

Competitive advantage through Six Sigma at plastic injection molded parts manufacturing unit

Abstract: Purpose The purpose of this paper is to illustrate the successful application of Six Sigma at a small and medium scale plastic parts manufacturing unit. Overall operational excellence is one of the foundations of global competiveness. Indian industries are also keeping up with achieving and maintaining operational excellence through different improvement tools and methodologies. Plastic parts manufacturing industries in India are also on the move to increase their overall quality, productivity and profitabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 40 publications
0
15
0
5
Order By: Relevance
“…Noori and Latifi ( 2018) used Lean Six Sigma to reduce defects in the grinding process of automotive engine manufacturing in Iran. Desai and Prajapati (2017) demonstrated the application of Six Sigma for competitive advantage through plastics moulding-related defect reduction in Indian small-scale industries. Bharathi et al (2017) applied lean to reduce welding defects in valve components.…”
Section: Methodsmentioning
confidence: 99%
“…Noori and Latifi ( 2018) used Lean Six Sigma to reduce defects in the grinding process of automotive engine manufacturing in Iran. Desai and Prajapati (2017) demonstrated the application of Six Sigma for competitive advantage through plastics moulding-related defect reduction in Indian small-scale industries. Bharathi et al (2017) applied lean to reduce welding defects in valve components.…”
Section: Methodsmentioning
confidence: 99%
“…Bersamaan dengan tinggnya komponen cacat, maka jumlah komponen yang harus diproduksi akan semakin banyak pula (Darshak, 2017).…”
Section: Pendahuluanunclassified
“…Six Sigma merupakan suatu pendekatan improvement yang bertujuan untuk mencari dan mengeliminasi penyebab kesalahan atau defect dalam proses bisnis dan fokus pada output proses yang kritis bagi konsumen. Six Sigma dikenal sebagai metode peningkatan kualitas yang paling efektif, dan penggunaannya menunjukkan tren positif (Darshak, 2017).…”
Section: Pendahuluanunclassified
“…Thirdly, the problem involves modelling the interaction between the production process and human factors. Previous studies have shown that the production process and human resource management practices cause lean to fail or succeed in manufacturing systems (Worley and Doolen, 2015;Desai and Prajapati, 2017). Most, if not all, manufacturing systems have human beings, whose behaviours, decisions, attitudes, commitment, mind-sets, motives, as well as (in)actions affect and are affected by the system they operate in.…”
Section: Hybrid Simulation Modellingmentioning
confidence: 99%